610 Technical challenges in monocyte-derived dendritic cell vaccine manufacturing; a QI project. (9th November 2020) - Reddy, Opal; Panch, Sandhya; Pham, Chauha; Sall, Mame Thioye; Tran, Minh; Highfill, Steven; West, Kamille; Jin, Ping; Jin, Haksong; Brenner, Malcolm; Berzofsky, Jay; Stroncek, David; et al.
Abstract : Background: With the explosive growth of cancer immunotherapies, cancer vaccines have been in the spotlight for their ability to turn cold tumors hot. Particularly, dendritic cell vaccines (DCV) are capable of harnessing the immune system to recognize single or multiple epitopes as they are professional antigen presenting cells. However, DCVs have not been recognized as the platform of choice in many studies due to relatively high cost, difficulty in standardizing manufacturing methods and risk of product inconsistency. We have been using monocyte-derived DCs transduced with an adenovirus vector expressing HER2/neu in a clinical trial to treat HER2-expressing cancers. The vaccine was administered on weeks 0, 4, 8, 16 and 24 at 4 different dose-levels; 5 × 10E6, 10 × 10E6, 20 × 10E6 and 40 × 10E6 viable cells. The clinical outcome of the study is under analysis. 1 To further optimize the safety and consistency of DCV, we reviewed the issues encountered in a first-in-human clinical trial during the manufacture of these cells at the NIH Clinical Center. Methods: Manufacturing records of NCT01730118 A Phase I Study of an Autologous DCV Targeting HER2 in Solid Tumors were reviewed to identify any complications or deviations encountered during manufacturing from apheresis to delivery of the fresh DCVs (figure 1 ). Results: Between April 2013 and October 2019, 134 vaccines were manufactured for 33 patients. A total of 113 (84%) DCVs were administered, with 103 (91%) of those meeting release criteria, and the remaining administered under authorized medical exception (AME). All patients underwent a single apheresis collection with 18 (median, range 15–20) liters processed and a goal of 6 aliquots (333 × 10E6 monocytes/vial). Dual lumen catheterization was required in 23 (70%) patients, and all procedural reactions required no or minimal intervention. Summaries enumerate aberrancies encountered during the manufacturing process (table 1 ). Overall, interpatient variabilities may have contributed to 92 (78%) events, while 26 (22%) events arose in a 'controllable', patient-unrelated environment. Conclusions: In spite of the variable events encountered during the manufacturing process, the majority of products were administered successfully. Patient-related variabilities were linked to most of the events. Future studies should be designed to minimize the impact of such variabilities on DCVs to provide high-quality personalized therapies. Manufacturing one large lot of DCs and cryopreserving enough aliquots for the entire study and the incorporation of an automated, closed cell culture system may reduce the aforementioned incidents and improve product quality. Acknowledgements: This study was supported by the NIH Clinical Center and Center for Cancer Research, the National Cancer Institute. The authors are indebted to the staffs at NIH Clinical Center and the patients. Ethics Approval: The study was approved by NCI/NIH Institutional Review Board (#534360, 13C0016). References: Maeng, H.M., et al., Preliminary results of a phase I clinical trial using an autologous dendritic cell cancer vaccine targeting HER2 in patients with metastatic cancer or operated high-risk bladder cancer (NCT01730118 ). Journal of Clinical Oncology 2019. 37(15_suppl): p. 2639–2639. Jin, P., et al., Plasma from some cancer patients inhibits adenoviral Ad5f35 vector transduction of dendritic cells. Cytotherapy 2018;20(5): p. 728–739.